2012
DOI: 10.1186/1471-2164-13-220
|View full text |Cite
|
Sign up to set email alerts
|

Widespread uncoupling between transcriptome and translatome variations after a stimulus in mammalian cells

Abstract: BackgroundThe classical view on eukaryotic gene expression proposes the scheme of a forward flow for which fluctuations in mRNA levels upon a stimulus contribute to determine variations in mRNA availability for translation. Here we address this issue by simultaneously profiling with microarrays the total mRNAs (the transcriptome) and the polysome-associated mRNAs (the translatome) after EGF treatment of human cells, and extending the analysis to other 19 different transcriptome/translatome comparisons in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 62 publications
8
115
1
Order By: Relevance
“…5A). Interestingly, CPX treatment resulted in marked fluctuations of the inducible HSP72 mRNA at the transcriptome level, while the changes at the level of translatome were somewhat buffered, again exemplifying the general uncoupling between transcriptome and translatome responses (Tebaldi et al, 2012). At the protein level, CPX caused a robust reduction of HSP90 expression (Fig.…”
Section: Iron Chelators Inhibit Hsp90 Translation In Neuroblastomamentioning
confidence: 82%
See 1 more Smart Citation
“…5A). Interestingly, CPX treatment resulted in marked fluctuations of the inducible HSP72 mRNA at the transcriptome level, while the changes at the level of translatome were somewhat buffered, again exemplifying the general uncoupling between transcriptome and translatome responses (Tebaldi et al, 2012). At the protein level, CPX caused a robust reduction of HSP90 expression (Fig.…”
Section: Iron Chelators Inhibit Hsp90 Translation In Neuroblastomamentioning
confidence: 82%
“…To enable a comprehensive overview of the gene expression response upon CPX treatment, a genome-wide multilevel transcriptome and translatome analysis was performed (Arava et al, 2003;Tebaldi et al, 2012). The polysomal mRNA (i.e., the mRNAs engaged in translation -the translatome) and the total mRNA (the total amount of transcribed mRNAs-the transcriptome) from CHP134 control cells and cells treated with 5 mM CPX for 90 minutes were extracted and quantified with gene expression microarrays.…”
Section: Iron Chelators Inhibit Hsp90 Translation In Neuroblastoma Rementioning
confidence: 99%
“…Microarray technologies assessing global mRNA levels in cells are only partially valid because posttranscriptional mechanisms dramatically affect protein levels in the proteome. Recent studies showed that ∌30% of protein levels actually correspond to mRNA levels at steady-state, suggesting that mechanisms solely regulating gene transcription or mRNA stability do not necessarily affect protein levels in cells and that changes in mRNA expression profiles frequently do not correspond to those seen in the cell's proteome (5,6).…”
Section: Posttranscriptional and Translational Control Of Gene Regulamentioning
confidence: 99%
“…Therefore, the ''translatome'' is increasingly investigated using analytical approaches that provide substantial and somewhat surprising new information [5]. The translatome represents an intermediate level in the regulation of gene expression, between the transcriptome and proteome, and reflects interactions of mRNAs with polysomes [6]. Techniques for translatome analyses include polysome [5] and ribosome profiling (ribosome protection assays) [1,7].…”
Section: Introductionmentioning
confidence: 99%